2011
DOI: 10.1002/btpr.682
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics modeling of mass transfer behavior in a bioreactor for hairy root culture. I. Model development and experimental validation

Abstract: A two-dimensional axisymmetric computational fluid dynamics (CFD) model based on a porous media model and a discrete population balance model was established to investigate the hydrodynamics and mass transfer behavior in an airlift bioreactor for hairy root culture.During the hairy root culture of Echinacea purpurea, liquid and gas velocity, gas holdup, mass transfer rate, as well as oxygen concentration distribution in the airlift bioreactor were simulated by this CFD model. Simulative results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Wang and Wang [12] investigated mass transfer in bubble column with the coupled CFD-PBM model and showed that the CFD-PBM coupled model could predict effectively the hydrodynamics and mass transfer. Liu et al [13] performed CFD-PBM coupled simulations of airlift bioreactor for hairy root culture and presented good agreement between simulations and experiments in terms of bubble number density. Xing et al [14] investigated the ability of the CFD-PBM coupled model to account for the effect of viscosity on the gas holdup in a bubble column.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wang and Wang [12] investigated mass transfer in bubble column with the coupled CFD-PBM model and showed that the CFD-PBM coupled model could predict effectively the hydrodynamics and mass transfer. Liu et al [13] performed CFD-PBM coupled simulations of airlift bioreactor for hairy root culture and presented good agreement between simulations and experiments in terms of bubble number density. Xing et al [14] investigated the ability of the CFD-PBM coupled model to account for the effect of viscosity on the gas holdup in a bubble column.…”
Section: Introductionmentioning
confidence: 88%
“…PBM is an effective method to calculate BSD for gas-liquid flows on the condition that bubble coalescence and breakup models are provided as model closures. Many researchers have used the coupled CFD-PBM model to predict the hydrodynamics and mass transfer in multiphase reactors [9][10][11][12][13][14]. Their studies showed that a better agreement between simulations and experiments was obtained when BSD was considered compared to using a constant mean bubble diameter.…”
Section: Introductionmentioning
confidence: 99%
“…CFD implementations and their simulations are a numerical tool to solutions of Navier–Stokes equations describing fluid characteristics, dynamics, and turbulences in a bioreactor. Kaiser et al presented numerical simulations of fluids in wave bag bioreactors and Liu et al established a comprehensive 2D axisymmetric CFD model to investigate hydrodynamics, oxygen distribution, and mass transfer in an ALR using hairy roots of Echinacea purpurea for experimental comparison. During cultivation several process parameters mostly properties of the cultivation medium have to be monitored continuously.…”
Section: Process Control Management and Modelingmentioning
confidence: 99%
“…A continuous flow of research can be observed in the past few years, which reveals the development of several mathematical models that efficiently describe the nutrient uptake, mass transfer, and gas distribution in different layers and their effect on tissue growth (Mairet et al 2010;Liu et al 2011;Palavalli et al 2012). As known, the tissue attains a nonlinear growth pattern, and one cannot understand the process by focusing only on a single or couple of growth parameters on any one scale.…”
Section: Growth Simulations and Modelingmentioning
confidence: 99%
“…With this view, nowadays, bioreactor technology utilizes engineering principles and mathematical formulations for mass production. Various research groups are working on issues like optimization of physical, biological, and chemical culture conditions (Prakash et al 2010;Mehrotra et al 2013a;Stiles and Liu 2013), offline and/or online measurement of growth (Uozumi 2004), mass transfer behavior (Liu et al 2011), synergistic effects of various physical and chemical parameters on growth, downstream processing (intracellular/extracellular), and product recovery (Bhagyalakshmi and Thimmaraju 2009;2012) in the course and/or at the end of scale-up. This may fairly help in filling the gap between capital cost and the benefits of technology at industrial scale (Stiles and Liu 2013).…”
Section: Bioreactor Technologymentioning
confidence: 99%